Analysis of Entrepreneurial Skill Development of Disadvantaged Group Entrepreneurs - Lokhande, Murlidhar A. (Prabandhan: Indian Journal of Management, 2017)
Entrepreneurship is considered as a panacea to socioeconomic problems. Small enterprises not only provide self-employment, but help in correcting regional disparities and more equal distribution of wealth. Entrepreneurship development among weaker sections, that is, scheduled castes and scheduled tribes, is the need of the hour in the present context of privatization. The disinvestment policies of the government have adverse effects on generation of employment opportunities in the public sector. Obviously, the most affected people are from scheduled castes, scheduled tribes, and other backward castes for which there are reservations in government jobs. The socioeconomic backwardness of scheduled castes and tribes, VJNT/NT, other backward classes and ultra poor from upper classes can be found in their dependence on agriculture, illiteracy, lower awareness levels, incidence of poverty, and underemployment. I attempted to probe into the research question such as whether there is an association between demographic characteristics and entrepreneurship development of people from marginalized groups ? The study inferred that there was an association between gender, social status, marital status, education, occupational background, entrepreneurship development programme except age of the respondents. The study suggested that special EDPs should be framed to train disadvantaged group entrepreneurs. In addition, necessary support of finance, infrastructure, and marketing should be extended to the entrepreneurs adequately and timely.